Tel Dor in the Middle Bronze Age and Maritime Adaptation along the Carmel Coast - Yasur-Landau, Assaf; Houghtalin, Chandler; Runjajić, Marko; Dunseth, Zachary; Shahack-Gross, Ruth (2024)
A newly excavated, well-built, Middle Bronze (MB) II-III coastal structure at Tel Dor provides a fresh glimpse into the turbulent settlement history of the Carmel Coast in the first half of the 2nd millennium b.c.e. The structure, incorporating a massive ashlar orthostat, was built in the MB I-II transition or MB II and existed for more than a century before its collapse during the MB III. A tight cluster of radiocarbon data indicates its destruction ca. 1600-1550 b.c.e. As the first Middle Bronze Age structure extensively excavated at Dor, it fills a lacuna in the site’s history. Other Middle Bronze Age finds enable a reconstruction of Dor’s anchorages and create a narrative of settlement patterns on the Carmel Coast, tightly connected with contemporary maritime activities, and reflecting a resilient settlement system devoid of urban centers.
Keywords: Canaanites; Carmel Coast; Middle Bronze Age; Tel Dor